Neurological features of epilepsy, ataxia, sensorineural deafness, tubulopathy syndrome. (8th August 2013) - Cross, J Helen; Arora, Ruchi; Heckemann, Rolf A; Gunny, Roxana; Chong, Kling; Carr, Lucinda; Baldeweg, Torsten; Differ, Ann‐Marie; Lench, Nicholas; Varadkar, Sophie; Sirimanna, Tony; Wassmer, Evangeline; et al.
Abstract : Aim: Recently, we reported a previously unrecognized symptom constellation comprising epilepsy, ataxia, sensorineural deafness, and tubulopathy (EAST syndrome) associated with recessive mutations in the KCNJ10 gene. Here, we provide a detailed characterization of the clinical features of the syndrome to aid patient management with respect to diagnosis, prognostic counselling, and identification of best treatment modalities. Method: We conducted a retrospective review of the detailed neurological and neuroradiological features of nine children (four females, five males; age range at last examination 6–20y) with genetically proven EAST syndrome. Results: All children presented with tonic–clonic seizures in infancy. Later, non‐progressive, cerebellar ataxia and hearing loss were noted. Whilst seizures mostly responded well to treatment, ataxia proved to be the most debilitating feature, with three patients non‐ambulant. All available magnetic resonance imaging (MRI) revealed subtle symmetrical signal changes in the cerebellar dentate nuclei. Moreover, four patients had a small corpus callosum and brainstem hypoplasia, and three had a small spinal cord. Regional quantitative volumetric analysis of the images confirmed the corpus callosum and brainstem hypoplasia and showed further patterns of variation from the norm. Interpretation: The neurological features of EAST syndrome appear to be non‐progressive, which is important for prognostic counselling. The spectrum of EAST syndrome includes consistent abnormalities on brain MRI, which may aid diagnosis. Further longitudinal documentation is required to determine the true natural history of the disorder. Abstract : This article is commented on by Stivaros on pages783–784 of this issue.